Effect of Dietary N‐acyl Homoserin Lactonase on the Immune Response and the Gut Microbiota of Zebrafish, Danio rerio, Infected with Aeromonas hydrophila. Issue 2 (April 2014) - Cao, Yanan; Liu, Yuchun; Mao, Wei; Chen, Ruidong; He, Suxu; Gao, Xiuhua; Zhou, Zhigang; Yao, Bin
Abstract Quorum sensing interference is a novel strategy in bacterial disease control. Degradation of quorum sensing signal molecules, such as N‐acyl homoserine lactones (AHLs), by enzymes is a potential interfering method. In this study, the in vivo effect of an N‐acyl homoserine lactonase from Bacillus sp. B546, AiiAB546, on the protection of zebrafish, Danio rerio, against Aeromonas hydrophila infection was first investigated by co‐feeding. The short‐term immune responses and the long‐term effects on the gut microbiota of zebrafish were analyzed by quantitative polymerase chain reaction (qPCR) and denaturing gradient gel electrophoresis (DGGE), respectively. The results showed that the expression levels of some anti‐infectious immunity‐related factors, including interleukin 10 (IL‐10), toll‐like receptor 5b (TLR5b), and inducible nitric oxide synthase 2a (iNOS2a) that were related to A. hydrophila virulent factors under regulation of quorum sensing, were more susceptible to the addition of AiiAB546. It indicated that AiiAB546 may attenuate the infection of A. hydrophila by interfering with quorum sensing. A. hydrophila was not detected in the enzyme co‐feeding diet group, which might be due to its inability to adhere to the gut with enzyme interference. This study revealed that AiiAB546 as a feed additive might represent a novel biocontrol agent in aquaculture; however, the topic merits further investigations using fish species of commercial interest.